Transport sector decarbonisation in the Global South: A systematic literature review - Nnaemeka Vincent Emodi; Chukwumerije Okereke; Fidelis Ibiang Abam; Ogheneruona Endurance Diemuodeke; Kesiena Owebor; Uchenna Alexander Nnamani (Energy Strategy Reviews, 2022)
Decarbonising the transport sector in the Global South presents an opportunity to contribute towards achieving net-zero by mid-century. Several studies have modelled different pathways to decarbonise the transport system, but the consensus is unclear due to the heterogeneous nature of transport technologies, infrastructure, locations, and consumers. In this sense, this study applies a systematic quantitative review to investigate the progression of low carbon transport sector and identified how the sector can decarbonise in an increasingly carbon-constrained world. The results show that while scholarly outputs are taking an upward trend, the geographic distribution of studies is uneven, and the outcomes of decarbonisation vary across developing countries. The study reveals that the decarbonisation of the transport sector presents challenges that are associated with revenue generation, funding of transition policies, competition for alternative fuels, crowding out of low-income consumers and potential rebound effects on travel behaviour. Therefore, the decarbonisation of the transport sector requires special mechanisms that are monitored and adjusted over time. The study highlights key cost-effective options for the decarbonisation of the transport sector while identifying knowledge gaps in the existing literature for future studies.